Novel insights into myocardial fibrosis in patients with new onset ST-elevation myocardial infarction following percutaneous coronary intervention through enhanced cardiac magnetic resonance imaging: a prospective cohort study - Temilola J. Oketunbi; Jun Wang; Bin Ding; Xilong Song; Yao Li; Hongwei Song; Xiaojun Shi; Sigang Hu; Dasheng Gao; Hongju Wang; Miaonan Li (BMC Cardiovascular Disorders)
Abstract Background Myocardial fibrosis is a prevalent pathological hallmark of a diverse range of chronic and acute cardiovascular disorders. However, the relevant literature currently provides limited evidence regarding the determinants of myocardial fibrosis severity in patients with new-onset ST-elevation myocardial infarction (STEMI) following successful emergent percutaneous coronary intervention (PCI) utilizing contrast-enhanced cardiac magnetic resonance imaging (CE-CMR). Methods We prospectively enrolled a cohort of 78 patients who presented with new-onset ST-segment elevation myocardial infarction and who underwent successful emergent PCI within 12 h from the onset of symptoms. Late gadolinium-enhanced LGE (LGE) was quantified via CE-CMR, and patients were categorized into two groups on the basis of the median LGE value. Results The median LGE was 16% (IQR 12 to 24). Compared with patients with LGE below the median (n = 37), those with LGE above the median (n = 41) presented significantly reduced left ventricular global radial strain(GRS), global circumferential strain(GCS), and global longitudinal strain(GLS) (all p < 0.05). The infarcted radial segment (IRS), infarcted circumferential segment (ICS) and infarcted longitudinal segment (ILS) were significantly reduced in patients with greater LGE (all p < 0.05). The occurrence rates of microvascular obstruction (MVO) (p < 0.001) and wall motion abnormality (WMA) (p < 0.01) were significantly greater in patients with a greater extent of LGE, despite successful reperfusion therapy. LGE exhibited a moderate negative correlation with the global circumferential segment (r=-0.547, p < 0.001) and a weak negative correlation with both the global radial segment and the global longitudinal segment (r=-0.434, p < 0.001; r=-0.437, p < 0.001). In the multivariable linear regression analysis model, the Gensini score (β = 0.258; p < 0.01), LVEF% (β=-0.269; p < 0.05), MVO (β = 0.343; p < 0.001) and GRS (β = 0.227; p < 0.05) emerged as robust predictors of myocardial fibrosis. Conclusion The present study revealed a correlation of cardiac pathological structure, microcirculation, and myocardial fibrosis in the context of acute myocardial infarction. Therefore, this study provides theoretical evidence from a pathological perspective regarding the progression of myocardial fibrosis in patients with new-onset STEMI following successful PCI. Trial registration The trial was registered in the Chinese Clinical Trial Registry (ChiCTR2400080282; January 25th, 2024).